DETERMINANT ANALYSIS OF STUNTING INCIDENCE OF TODDLERS AGED 12-59 MONTHS IN WEST AND EAST KOYA VILLAGES, JAYAPURA CITY - Natalia Paskawati Adimuntja; Asriati Asriati (Jambura Journal of Health Sciences and Research, 2023)
Double burden atau masalah gizi ganda salah satunya ditandai dengan tingginya prevalensi stunting. Prevalensi stunting pada balita di Indonesia yakni 27,7%. Prevalensi stunting di Papua sebesar 29,5%. Sedangkan data prevalensi kota Jayapura yakni sebesar 22,9%. Kebaruan penelitian ini karena meneliti tentang determinan kejadian stunting pada balita usia 12-59 bulan. Penelitian ini bertujuan untuk mengetahui determinan kejadian stunting pada balita usia 12-59 bulan di Kelurahan Koya Barat dan Timur Kota Jayapura. Jenis penelitian yang digunakan adalah penelitian observasional dengan rancangan penelitian cross sectional study. Sampel penelitian ini berjumlah 100 responden balita usia 12-59 bulan di kelurahan koya barat dan timur yaitu sebanyak 769 balita. Wawancara mengggunakan kuesioner dan recall 24 jam untuk menilai keragaman pangan. Uji statistik yang digumakan untuk melihat hubungan yaitu uji chi-square (x2) dan uji Fisher Exact jika nilai expect countnya 5%. Hasil penelitian diperoleh bahwa balita yang mengalami stunting sebanyak 13 orang (13,0%) dan yang tidak stunting sebanyak 87 orang (87,0%). Hasil analisis bivariat menunjukkan bahwa variabel keragaman pangan (p-value=0,024) signifikan berhubungan dengan kejadian stunting, sedangkan pendidikan ibu (p-value=0,763), pekerjaan ibu (p-value=0,120), pemberian ASI Eksklusif (p-value=0,765), status imunisasi (p-value=0,509), dan penyakit infeksi (p-value=0,367) tidak signifikan berhubungan dengan kejadian stunting pada balita usia 12-59 bulan di Kelurahan Koya Barat dan Timur Kota Jayapura. Kesimpulan penelitian ini yaitu keragaman pangan berhubungan dengan kejadian stunting pada balita usia 12-59 bulan di Kelurahan Koya Barat dan Timur Kota Jayapura.Kata kunci: Determinan; Stunting; Balita 12-59 bulan AbstractDouble burden or double nutrition problem, one of which is characterized by a high prevalence of stunting. The majority of stunting in children under five in Indonesia is 27.7%. The bulk of stunting in Papua is 29.5%. Meanwhile, the prevalence data for Jayapura city is 22.9%. The novelty of this study is because it examines the determinants of stunting incidence in toddlers aged 12-59 months. This study aims to determine the determinants of stunting incidence in toddlers aged 12-59 months in West and East Koya Villages of Jayapura City. The type of research used is observational research with a cross-sectional study design. The sample of this study was 100 respondents under the age of 12-59 months in the west and east Koya villages, namely 769 toddlers. Interviews used 24-hour questionnaires and recall to assess food diversity. The statistical tests used to see the relationships are the chi-square test (x2) and the Fisher Exact test if the expected count value is 5%. The results of the study obtained 13 children (13.0%) children who were not stunted (87.0%) and 87 people who were not checked (87.0%). The results of the bivariate analysis showed that the variables of food diversity (p-value = 0.024) were significantly related to the incidence of stunting, while maternal education (p-value = 0.763), maternal occupation (p-value = 0.120), exclusive breastfeeding (p-value = 0.765), immunization status (p-value = 0.509), and infectious diseases (p-value = 0.367) were not significantly associated with the incidence of stunting in toddlers aged 12-59 months in West and East Koya Villages, Jayapura City. This study concludes that food diversity is related to the incidence of stunting in toddlers aged 12-59 months in West and East Koya Villages, Jayapura City.Keywords: Determinants; Stunting; Toddlers 12-59 months